2009
DOI: 10.1093/brain/awp269
|View full text |Cite
|
Sign up to set email alerts
|

Executive function and fluid intelligence after frontal lobe lesions

Abstract: Many tests of specific ‘executive functions’ show deficits after frontal lobe lesions. These deficits appear on a background of reduced fluid intelligence, best measured with tests of novel problem solving. For a range of specific executive tests, we ask how far frontal deficits can be explained by a general fluid intelligence loss. For some widely used tests, e.g. Wisconsin Card Sorting, we find that fluid intelligence entirely explains frontal deficits. When patients and controls are matched on fluid intelli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
227
3
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(269 citation statements)
references
References 73 publications
(107 reference statements)
24
227
3
4
Order By: Relevance
“…Considerable controversy exists about precisely what is measured by tests of executive function. It has been suggested that tests used to assess executive functioning may not reflect a unique aspect of functioning but may be better explained in terms of other cognitive processes involved in test performance, such as verbal abilities, processing speed, or even intelligence (Greenaway et al, 2009;Roca et al, 2010). Hence, our executive domain may not be measuring a uniform set of processes, which may explain why only a small network was commonly expressed.…”
Section: Discussionmentioning
confidence: 99%
“…Considerable controversy exists about precisely what is measured by tests of executive function. It has been suggested that tests used to assess executive functioning may not reflect a unique aspect of functioning but may be better explained in terms of other cognitive processes involved in test performance, such as verbal abilities, processing speed, or even intelligence (Greenaway et al, 2009;Roca et al, 2010). Hence, our executive domain may not be measuring a uniform set of processes, which may explain why only a small network was commonly expressed.…”
Section: Discussionmentioning
confidence: 99%
“…Delis et al, 2001). The Hotel Task (Manly et al, 2002) was included to increase ecological validity of test measures, as it mimics real-life multitasking situations, demonstrating acceptable ecological validity, and sensitivity in detecting ED in various disorders (Roca et al, 2008(Roca et al, , 2010Torralva et al, 2012). Similarly, the UCSD Performance-Based Skills Assessment (UPSA) (Patterson et al, 2001), originally developed for studies of schizophrenia (Patterson, Goldman, McKibbin, Hughs & Jeste, 2001;Mausbach, Harvey, Goldman, Jeste & Patterson, 2007), was included because it targets "reallife" multitasking situations, as subjects role-play with the examiner in three functional domains (communication, finance, and transportation).…”
Section: Active Control Conditionmentioning
confidence: 99%
“…The exact nature of these processes is unknown but a failure to adopt a strategy on the HSCT in individuals with schizophrenia is similar to that observed in right lateral frontal patients, further implicating this region in schizophrenia pathology. However, although the right lateral frontal region is implicated in strategy use (Miller & Tippett, 1996;Robinson et al, 2015;Roca et al, 2010) and inhibition (Aron, Fletcher, Bullmore, Sahakian, & Robbins, 2003;Aron et al, 2014) The current study, to the authors' knowledge, is the first to address the nature of completions and errors on the initiation section of the HSCT. The patients with schizophrenia produced a greater number of uncommon, bizarre, or incorrect responses, although the composite measures were no longer significant after controlling for the baseline cognitive measures.…”
Section: Discussionmentioning
confidence: 94%